A 402-output TFT-LCD driver IC with power control based on the number of colors selected. - Itakura, T. (IEEE Journal of solid state circuits)
A 402-output thin-film-transistor liquid crystal display (TFT-LCD) driver integrated circuit (IC) with power control based on the number of colors to be displayed is described. To achieve this type of power control, reference voltage buffers are turned on and off according to the selected number of colors. In this architecture, the reference voltage buffers must drive 1-402 capacitive loads, corresponding to a capacitance of 30-12000 pF. Phase compensation using a zero formed with capacitive loads is proposed for the reference voltage buffers. The introduced zero has a fixed zero frequency for 1-402 loads. An operational amplifier with slew-rate enhancement is also proposed for the buffers. An experimental 402-output TFT-LCD driver IC was fabricated using a 0.6-μm CMOS technology. The chip size was 2.35 mm × 18.1 mm. The quiescent current dissipation of the analog section including decoders was 529 μA for 262144 colors, 182 μA for 4096 colors, and 112 μA for 512 colors for a 5-V supply.